PERSEPSI MASYARAKAT MINAHASA TENTANG PASAR “EXTREME” TOMOHON - MESRA, ROMI; Hidayat, Muhammad Fajar; Korlefura, Criezta; Tanaya, Anang Mulya (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2022)
One of the most famous markets in the Minahasa-North Sulawesi area nationally and internationally is also known as local wisdom known as the